Design General Hospital Data Warehouse Base on Nine Step Methodology - Leo Mahadya Suta, Ida Bagus; Agung Surya Mahendra, I Gusti Ngurah; Sudarmojo, Yanu Prapto (International Journal of Engineering and Emerging Technology, 2019)
Data warehouse is a method used to hold and analyze data in large number. The analysis can be viewed from several different dimensions or points of view. The application of data warehouse technology can overcome the problems and needs of executive at Genral Hospital in conducting analysis of large amounts of patient data, especially data inpatient and outpatient care. The data warehouse design method is done by applying 9 step (Nine-Step Methodology) used by Kimball. The 9 stages are the selection process, selection, grain, identification and adjustment, fact selection, pre-calculation storage in the fact table, ensure dimension tables, select database durations, track changes from dimensions slowly, determination of priority and query model. The results of this study are in the form of schema design and data simulation warehouse by displaying inpatient and outpatient data based on time dimensions, patients reference, diagnosis, patient status, room, type of patient, condition of return, and district in the form of a table and graph